Audit keamanan sistem informasi pada bagian simda berdasarkan standart iso 27002: 2005 in Dinas Pendapatan Dan Pengelolaan Keuangan Daerah Lombok Barat - Atmajaya, Riyadi; Tanuwijaya, Haryanto; Sutomo, Erwin (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
The revenue and regional financial management ( dppkd ) one intansi implementing information technology as distributor information in released a report will generate by the revenue and financial management districts of West Lombok. The revenue and regional financial management (dppkd) one intansi implementing information technology as distributor information in released a report will generate by the revenue and financial management districts Of Wes Lombok, One framework used to that the audit it uses iso 27002: 2005 to know the security system information ongoing and methods used to stage the security system audit reference this is cisa , clause and scope used is clause 8 , 9, and 11 . The result of the security audit information system , obtained a list of the findings and recommendations to reduce security risk information from evidence and findings that is to improve security the the information system to the revenue and regional financial management Of West Lombok.